Memahami Estetika dari Sudut Pandang Desain Interior - Sofiana, Yunida (Bina Nusantara University, 2015)
The term aesthetic has always become part of design. Without aesthetic, design has just a functional object. Aesthetic in design, particularly in interior design, has been influenced by many factors, which are aesthetic value, aesthetic perception, and time frame. Aesthetic has subjective meaning related to time frame and objective meaning related to implementation of element and principles of design on aesthetic term. Aesthetic perception is how we judge and see the object using our own thinking and value. Time frame is where and when the aesthetic value happens. Interior design trend right now has been influenced by technology in many ways so the concept of modern design theme is always the best choice for designer. However, using modern theme as a design concept has to be implemented as a whole theme and related to aesthetical value so that the design will gain much appreciation from others. This paper used deductive method to explain the theory of aesthetic and the implementation of aesthetic value in interior design context. Design should speak louder than it looked.